Association between peer behaviors and family environment and pre-packaged sugar-sweetened beverage consumption among primary and secondary school students in Beijing - Li, Yiran; Meng, Lulu; Liang, Siyu; Zhang, Yan; Li, Wenjia; Duan, Jiali; Cao, Ruoxiang; Li, Jie; Huang, Liyu (Frontiers in Public Health, 2025)
BackgroundSugar-sweetened beverage (SSB) consumption among children and adolescents remains high worldwide. In China, most studies have examined either peer or family influences, but few have assessed their combined effects, particularly for pre-packaged SSBs.MethodsA cross-sectional study was conducted among 2,317 primary and secondary school students in Beijing between October and November 2024. Students and their caregivers completed paired questionnaires on pre-packaged SSB consumption and potential influencing factors. Multivariable logistic regression was used to examine associations between peer and family factors and SSB consumption, adjusting for demographic and behavioral covariates.ResultsIn the past week, 81.9% of students consumed at least one type of pre-packaged SSB. With the increase of age, the intake of SSBs increased in children. Fruit/vegetable beverages were the most commonly consumed beverages for primary school students, and tea beverages were the most commonly consumed beverages for secondary school students. Peer-influenced purchasing behavior (OR: 1.600,95% CI:1.318–1.941), peer-sharing behavior (OR: 1.373,95% CI:1.106–1.704), household accessibility (OR: 1.305,95% CI:1.085–1.570) and parental supportive attitudes toward SSBs (OR: 2.246,95% CI:1.691–2.981) were associated with high consumption of SSBs. Similar associations were observed for carbonated beverages, tea beverages, milk beverages, and other categories, though effect sizes varied.ConclusionPeer behaviors and family environments substantially influence pre-packaged SSB consumption among children and adolescents in Beijing. Targeted interventions should include banning SSB sales in school canteens, introducing warning labels on high-sugar beverages, and promoting parental education to reduce home availability.